PEMBERDAYAAN SUMBER DAYA MANUSIA DALAM MENGOPTIMALKAN FUNGSI BADAN USAHA MILIK DESA. DI DESA GUAAN KECAMATAAN MOAAT KABUPATEN BOLAANG MONGONDOW TIMUR - Rafael, Untu Geraldy; Posumah, Johnny Hanny; Plangiten, Novva (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This study aims to "Describe, interpret how the effort of empowering human resources inoptimizing the function of Village Owned Enterprises (BUMdes)".This research uses descriptive method of qualitative approach, and data collection technique used withobservation, interview technique and documentation. The number of informants in this study as many as 5people. In this study using the model of empowerment (strengthening) of human resources in theorganization BUMDes.The results of this study indicate that the first stage of desire in the empowerment model is running well.The desire in the empowerment effort (reinforcement) is currently only done by the village government thatis Sangadi to the board of BUMDes with this seen from the study activity of appeal outside the region. Stageof confidence in empowerment not yet run well. The trust given by the government and the community isvery full given to people who are appointed directly and specifically in the management and developmentactivities of BUMDes, but the trust through education and training which is the stage of empowerment(reinforcement) has not been made specifically to every board BUMDes. Stage of confidence inempowerment model still must be upgraded again, confidence every board of BUMDes only limited able tomanage but matter of creativity and innovation in management and development of BUMDes until now notyet created. The credibility stage in the empowerment model is not a problem in management anddevelopment and the board has been able to show their performance through BUMDes activities that arestill ongoing. At this stage, the responsibilities of the board should be improved in completing the tasks andresponsibilities that have been given, although the government often assists it, but the board is fullyresponsible in the management and development of BUMDes. At this stage, communication within theorganization should be the attention of the government and the board of BUMDes must have a formalmeeting to be attended by BPD, the government and the board that contains the performance reportperformance agenda of BUMDesKeywords: Empowerment (strengthening), Human Resources, Village Owned Enterprises (BUMdes)